Factors influencing the growing number of victims of fraud and pyramid schemes and methods to counter them - Turetsky, Н.Н. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
Financial pyramids and fraudulent schemes aimed at an irretrievable extraction of money from gullible citizens have become highly widespread in recent years. It has created a real threat to the material well-being of citizens and the economic development of the state. The article considers the main reasons why people are willing to invest their savings in the activities of dubious organizations in exchange for promises of high profits. The author identifies such acute problems as the low level of financial literacy, the high percentage of the population living below the poverty line, the incorrect calculation of average income, and the definition of the subsistence level. As a result of the analysis of the current situation, the article presents statistical data, normative legal acts, and the experience of foreign countries with developed economies the possible ways of solving the mentioned problems.